UPAYA MENINGKATKAN KEMAMPUAN MEMBACA, MENULIS DAN MENGHITUNG MELALUI REMEDIAL TEACHING BAGI ANAK TUNAGRAHITA RINGAN DI WISMA PAULO 6 YAYASAN BHAKTI LUHUR MALANG - Sri Wahyuni; Stefanus Ngea (Jurnal Pelayanan Pastoral, 2023)
People with mental retardation often experience delays in both physical and mental development so that they require intervention to make up for the delay. The Bhakti Luhur Integrated Program or PTBL is the flagship program of the Bhakti Luhur Foundation to help mentally retarded people improve the disabilities of persons with disabilities, one of which is the disability in the field of self-help bathing. This study intends to assess whether PTBL training can improve the ability to help self-help bathing mentally retarded children at Wisma Dewandaru Malang. The research method used is a quantitative research method with the type of pre-experimental research because there is no control group with a one group pretest and posttest design. It is hoped that this research can become a reference for other researchers to train other mentally retarded people who have problems with bathing themselves. The results obtained were as follows: for YT respondents, the pre-test score was 52 and the post-test was 65, so there was an increase of 13 points. the pre-test was 52 and the post-test score was 71.5 so there was an increase of 19.5 points, respondent P's pre-test score was 56.5 and the post-test was 77 so there was an increase of 20.5 points. If seen from the four respondents or subjects who experienced the highest increase, it was P with an increase of 20.5 points and the second place IS experienced an increase of 19 points, the third was LS with an increase of 15 points and the last was YT with 13 points